(2x-y)/5+(x+y)/3=6 (x+4y)=7-(2x-4y)/3 解二元一次方程组
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 06:59:47
(2x-y)/5+(x+y)/3=6(x+4y)=7-(2x-4y)/3解二元一次方程组(2x-y)/5+(x+y)/3=6(x+4y)=7-(2x-4y)/3解二元一次方程组(2x-y)/5+(x+
(2x-y)/5+(x+y)/3=6 (x+4y)=7-(2x-4y)/3 解二元一次方程组
(2x-y)/5+(x+y)/3=6 (x+4y)=7-(2x-4y)/3 解二元一次方程组
(2x-y)/5+(x+y)/3=6 (x+4y)=7-(2x-4y)/3 解二元一次方程组
(2x-y)/5+(x+y)/3=6
2/5*x-1/5*y+1/3x+1/3y=6
(2/5+1/3)x+(-1/5+1/3)y=6
11/15*x+2/15y=6
y=(6-11/15x)*15/2=45-11/2*x
(x+4y)=7-(2x-4y)/3
x+4y=7-2/3x+4/3y
(1+2/3)x+(4-4/3)y=7
5/3x+8/3y=7
5/3x+8/3(45-11/2*x)=7
x=113/13
y=45-11/2*x=-73/26
x+y/2+x-y/6=5 2(x+y)-3(x-y)=-2
6(x-y)-2(x+y)=14 3(x-y)+(x+y)=5
已知x-y/x+y=3,求代数式5(x-y)/x+y-x+y/2(x-y)
[2(x-y)^5-8(x-y)^2(x+y)+6y(x-y)^2]÷2(x-y)^2[2(x-y)^3-8(x-y)^2(x+y)+6y(x-y)^2]÷2(x-y)^2
3x+5y-(x+y)=6 2(x+y)-3x=-7
【2(x-y)^3-8(x-y)^2(x+y)+6y(x-y)^2】/2(x-y)^2=
把(x-y)看作一个整体,化解:5(x-y)+2(x-y)-4(x-y)= 3(x-y)把(x-y)看作一个整体,化解:5(x-y)+2(x-y)-4(x-y)=3(x-y)²-4(x-y)+7(x-y)-6(x-y)²=
{x+y=1 ,xy=-6{x(2x-3)=0,y=x²-1{(3x+4y-3)(3x+4y+3)=0,3x+2y=5{(x-y+2)(x+y)=0,x²+y²=8{(x+y)((x+y-1)=0,(x-y)(x-y-1)=0
2(2x+3y)(3x+2y)-(6x-y)(2x-5y)
x+y/2+x-y/3=6,4(x+y)-3(x-y)=-20
{(x+y)/2+(x-y)/3=6 4(x+y)-3(x-y)=-20
4(x+y)-3(x-y)=-20,2/x+y+3/x-y=6
(x+y)/2- x-y/2=6 3(x+y)=4(x-y)
x+y/3+x-y/2=6 4(x+y)-2(x-y)=40
{6(x-y)-7(x+y)=21 {2(x-y)-5(x+y)=-1
3(x+y)+2(x-y)=36 4(x+y)-5(x-y)=2
2(x+y)-3(x-y)=1 6(x+y)+(x-y)=51
{3(x+y)-4(x-y)=4 {x+y/2 + x-y/6=1